Performance of a moment resisting beam-column connection for precast concrete construction. (1st November 2021) - Baran, Eray; Mahamid, Mustafa; Baran, Mehmet; Kurtoglu, Metin; Torra-Bilal, Ines
Highlights: Seismic performance of a moment resisting precast concrete beam-column connection. Investigated connection method relies on steel components for force transfer. Connection method offers the potential to provide an acceptable seismic performance. Behavior of connection is influenced significantly by the steel plate anchorage detail. Simple detailing modifications improve strength, stiffness and energy dissipation characteristics of connection. Abstract: Seismic performance of a specific type of moment resisting precast concrete beam-column connection was investigated through reversed cyclic load tests. Structural steel components were incorporated with precast concrete beam and column elements in the experiments to provide a ductile moment resisting connection. Additionally, nonlinear finite element analysis (FEA) of typical monolithic and precast connections was performed to investigate the performance and failure modes of these connections. Concrete Damage Plasticity (CDP) model was used to capture nonlinearities in concrete under cyclic loading. Good agreement was achieved between experimental and numerical results, which indicates that the finite element model is capable of capturing failure modes of the investigated precast connections. Agreement between the experimental and numerical behaviors was valid in terms of both the global load–displacement response as well as the local response, such as the force within connection rods and the beam curvature. Behavior of the precast concrete connection was influenced significantly by the anchorage detail used for steel connection plates and the beam reinforcement detailing in the vicinity of the connection. Simple detailing modifications resulted in major improvements in the performance of connection in terms of strength, stiffness and energy dissipation characteristics.